(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Objective: This study aimed to compare postpartum infections and neonatal sepsis in relation to the timing of perioperative antibiotics at cesarean section. Material and Methods: This was a prospective randomized controlled trial in Monno Medical College & Hospital of Manikganj. 176 patients with singleton, live, term or near-term pregnancies fulfilling the inclusion and exclusion criteria were included in the study. All the patients underwent caesarean section between June 2014 to May 2015. The population was divided into two groups: Group - A (89 Patients) and Group –B (87 Patients). Group A (89) received injectable antibiotic Ceftriaxone 1 gm 30-60 minutes before skin incision and Group –B (87) received the same antibiotic after cord clamping. Rates of postoperative infections, endometritis, UTI, and wound infection (SSI) and neonatal sepsis were compared between two groups. Results: There were 176 patients enrolled and no demographic difference were observed between two groups. No significant difference was found between the groups for total infectious morbidity. Rates of endometrities (P=1.0), UTI (P=0.5), Febrile morbidity (P= 0.77), wound infection (SSI) (P=0.4), neonatal sepsis (P=0.77), NICU (P=0.1), NICU length of stay (P=0.67). Conclusions: Time of prophylactic antibiotic application does not change maternal infectious morbidity in cesarean section deliveries, preoperative prophylaxis application does not affect neonate morbidity rate as stated in literature. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(1): 18-23